IMPACT OF BMI ON COGNITIVE ABILITY AND SLEEP QUALITY IN ADOLESCENTS (Journal of Medical & Health Sciences Review, 2025)
This cross-sectional study examined the effect of Body Mass Index (BMI) on sleep quality and cognitive performance in 196 adolescents (12–20 years) from Lahore government schools and colleges, selected through convenience sampling. Eligible participants had no history of substance use, chronic illness, neurological or psychiatric disorders, sleep issues, or recent major life events. Data were collected using the Pittsburgh Sleep Quality Index, a Cognitive Assessment Questionnaire, and BMI calculations. Analysis with SPSS 25 showed most participants had poor sleep and average cognition, with no significant association between BMI and either sleep quality (p = 0.714) or cognition (p = 0.697). Findings suggest that factors other than BMI—such as behavioral, environmental, or psychosocial influences—may play a greater role in adolescent sleep and cognitive health.